Rozwiąż układ metodą podstawiania:
1).{3½x-2⅖y=1,1-------->½y+6=0,4x
2).{3-(x-2y)=2(x+4)------->5(x-2)=6(y-3)-4
3).{2x-y=0------->x+2y=5
4).{3(x+1)=y+2----->2(y-1)=6x
rozwiąż układ metoda przeciwnych współczynników:
1).{2x+y=3----->2x-3y= ₋1
2).{5x+y=3----->x-2y=4
3).{3x+2y=1---->2x+4y= ₋3
4).{5x=6(y-1)---->3x+5y=3
5).{3,4x-1⅓y=6---->2¾x+3=1½(y-2)

1

Odpowiedzi

2009-04-08T10:19:24+02:00
I.

2)
3-(x-2y)=2(x+4)
5(x-2)=6(y-3)-4

3-x+2y=2x+8
5x-10=6y-18-4

-x-2x+2y=8-3
5x-6y=10-18-4

-3x+2y=5
5x-6y=-12

-3x+2y=5
-6y=-5x-12/:(-6)

-3x+2y=5
y=5/6x+2

-3x+2(5/6x+2)=5
y=5/6x+2

-3x+10/6x+4=5
y=5/6x+2

-8/6x=1/:(-8/6)
x=6/8

y=21/8


3)
2x-y=0
x+2y=5

2x-y=0
x=5-2y

2(5-2y)-y=0
x=5-2y

10-4y-y=0
x=5-2y

-5y=-10/:(-5)
x=5-2y

y=2
x=5-2*2

y=2
x=1



4)
3(x+1)=y+2
2(y-1)=6x

3x+3=y+2
2y-2=6x

3x-y=-1
2y-6x=2

3x-y=-1
2y=2+6x/:2

3x-y=-1
y=6x

3x-6x=-1
y=6x

-3x=-1/:(-3)
y=6x

x=1/3
y=6*1/3

x=1/3
y=2

2)
5x+y=3/*2
x-2y=4

10x+2y=6
x-2y=4

11x=10/:11
x=10/11

x=10/11
y=18/11